Oxidative Degradation of Sulfathiazole by Fenton and Photo-Fenton Reactions - Salazar-Gonzalez, R (2014)
This article presents experimental results on 47 ?mol L-1 sulfathiazole (STZ) degradation by Fenton and photo-Fenton reactions using multivariate analysis. The optimal experimental conditions for reactions were obtained by Response Surface Methodology (RSM). In the case of the Fenton reactions there were 192 ?mol L-1 ferrous ions (Fe(II)) and 1856 ?mol L-1 hydrogen peroxide (H2O2), as compared with 157 ?mol L-1 (Fe(II)) and 1219 ?mol L -1 (H2O2) for photo-Fenton reactions. Under these conditions, around 90% of STZ degradation were achieved after 8 minutes treatment by Fenton and photo-Fenton reactions, respectively. Moreover, a marked difference was observed in the total organic carbon (TOC) removal after 60-min treatment, achieving 30% and 75% for the Fenton and photo-Fenton reactions, respectively. Acetic, maleic, succinic and oxamic acids could be identified as main Fenton oxidation intermediates. A similar pattern was found in the case of photo-Fenton reaction, including the presence of oxalic acid and ammonia at short periods of irradiation with UV-A. The calculated values of Average Oxidation State (AOS) corroborate the formation of oxidized products from the initial steps of the reaction. © 2014 Copyright Taylor and Francis Group, LLC.